Análise dos processos organizacionais de estágio supervisionado da UFES Campus Alegre - Curty, Wisley Braga (2018)
The supervised internship student in Brazil must be performed according to the legal precepts so that it is not classified as a labor activity and departs from its pedagogical purpose. To this end, it is necessary that the procedures involving the formalization of the practice be performed with excellence in all administrative areas. Every semester, several undergraduate students of the Federal University of Espírito Santo (UFES) campus Alegre do some kind of internship, and it is noted that the number of students has grown in recent years. Therefore, the administrative processes of formalization of the practice within the scope of UFES must properly take place so that the university is not subject to labor sanctions, since it is responsible for the internship agreement between student and university. However, this process is centralized at the top of the administrative structure, which may compromise the performance of activities in their mode of excellence. Therefore, this action research comprised a case study about the influence of hierarchical centralization on the administrative activity of supervised internship at UFES campus Alegre, intermediated by the Single Undergraduate Secretariat (SUGRAD). In the light of the methodology of administrative analysis of Antônio Cury (2005), through a qualitative and quantitative approach, the organizational processes of attending the student, signing of agreements with granting units, and formalization of an internship term (TCE). It was noticed that the influence of centralization stands out when it comes to the formalization of TCE. In this process, decentralization is an alternative to a service of excellence. In the others, semi-annual collective orientations directed to the academic community, as well as interventions in the stages and reorganization of the current processes may be able to increase the efficiency and organizational effectiveness. As a result, the results found subsidized the suggestion of an applicable technical product, which maximizes the management of internships in the campus, by proposing a manual containing guidelines, form and flowcharts that contemplate the local reality.